Changelings in Chicago: Southside Girls: Growing Up in the Great Migration. Issue 2 (1st June 2021) - Unknown
Abstract : Marcia Chatelain. 2015. Southside Girls: Growing Up in the Great Migration . Durham, NC: Duke University Press.